Предмет: Алгебра,
автор: tatyanaigorevna71
Упростите выражение:
1) (а-2)²
2)(а-3)*(а+3)
3)(х-1)*(х²+х+1)
4)2*(с-2)*(2+с)
5)(х²+3)²
6)(а-3)*(а+6)
tatyanaigorevna71:
Пожалуйста
Ответы
Автор ответа:
1
Ответ:
1)(a-2)²=a²-4a+4
2)(a-2)(a+2)=a²-4
3)(x-1)(x²+x+1)=x³-1
4)2•(c-2)(c+2)=2c²-8
5)(x²+3)²=x^4+6x²+9
6)(a-3)(a+6)= a²+6a-3a-18=a²+3a-18
Похожие вопросы
Предмет: Окружающий мир,
автор: Gabriella24
Предмет: Английский язык,
автор: Smail1937
Предмет: Русский язык,
автор: salisheva2012
Предмет: Окружающий мир,
автор: fjwgjerhnafj
Предмет: Қазақ тiлi,
автор: FoxyDiamond